Electromagnetics - Ellingson, Steven W. (Open textbook library., 2020)
Electromagnetics, volume 2 by Steven W. Ellingson is a 216-page peer-reviewed open textbook designed especially for electrical engineering students in the third year of a bachelor of science degree program. It is intended as the primary textbook for the second semester of a two-semester undergraduate engineering electromagnetics sequence. The book addresses magnetic force and the Biot-Savart law; general and lossy media; parallel plate and rectangular waveguides; parallel wire, microstrip, and coaxial transmission lines; AC current flow and skin depth; reflection and transmission at planar boundaries; fields in parallel plate, parallel wire, and microstrip transmission lines; optical fiber; and radiation and antennas. To express your interest in this book or series, please visit http://bit.ly/vtpublishing-updates Additional resources Problem sets and the corresponding solution manuals; Slides of figures used in and created for the book; LaTeX sourcefiles; Errata for Volume 2; Collaborator portal for the Electromagnetics series; Faculty listserv for the Electromagnetics series. An accessible version will be available in January 2020. The Open Electromagnetics Project Led by Steven W. Ellingson at Virginia Tech, the goal of the Open Electromagnetics Project is to create no-cost openly-licensed content for courses in engineering electromagnetics. The project is motivated by two things: lowering learning material costs for students and giving faculty the freedom to adopt, modify, and improve their educational resources. Books in this Series Electromagnetics, Volume 1 https://doi.org/10.21061/electromagnetics-vol-1 Electromagnetics, Volume 2 https://doi.org/10.21061/electromagnetics-vol-2